Eccrine sweat gland development and sweat secretion. Issue 9 (14th July 2015) - Cui, Chang‐Yi; Schlessinger, David
Abstract Eccrine sweat glands help to maintain homoeostasis, primarily by stabilizing body temperature. Derived from embryonic ectoderm, millions of eccrine glands are distributed across human skin and secrete litres of sweat per day. Their easy accessibility has facilitated the start of analyses of their development and function. Mouse genetic models find sweat gland development regulated sequentially by Wnt, Eda and Shh pathways, although precise subpathways and additional regulators require further elucidation. Mature glands have two secretory cell types, clear and dark cells, whose comparative development and functional interactions remain largely unknown. Clear cells have long been known as the major secretory cells, but recent studies suggest that dark cells are also indispensable for sweat secretion. Dark cell‐specific Foxa1 expression was shown to regulate a Ca2+‐dependent Best2 anion channel that is the candidate driver for the required ion currents. Overall, it was shown that cholinergic impulses trigger sweat secretion in mature glands through second messengers – for example InsP3 and Ca2+ – and downstream ion channels/transporters in the framework of a Na+‐K+‐Cl− cotransporter model. Notably, the microenvironment surrounding secretory cells, including acid–base balance, was implicated to be important for proper sweat secretion, which requires further clarification. Furthermore, multiple ion channels have been shown to be expressed in clear and dark cells, but the degree to which various ion channels function redundantly or indispensably also remains to be determined.